Kelayakan Bunga Rosella Dalam Pembuatan Lip Scrub - Sofia Daniati; Nurmala Qurin Anisa (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2020)
Rosella flowers are generally processed into tea. Important ingredients in this flower make rosella tea has many benefits for human health. The use of rosella flowers in making lipscrub is expected to be a new innovation in cosmetic products. The aim of this research is to create a lip scrub based on rosella flowers which functions to remove dead skin cells and moisturizes the lips. This research was conducted by means of literature, documentation, experiments and public testing. This experiment resulted in three products with different compositions. The three products have been tested publicly on the 30 panelists who have an age range of 17 to 40 years. From 30 panelists who have tried 3 lip scrub products. It was found that most of the panelists preferred products with a composition of 1.8 grams of roselle flower powder, 1.7 grams of vaseline and 3.2 grams of honey. This can be seen from the public test average calculation score on the favorite indicator, namely 1.8. So it can be concluded that Rosella flower lipscrub has the opportunity to be developed as a new innovation in the world of cosmetics.